2002
DOI: 10.1034/j.1600-079x.2002.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the protective effects of melatonin and vitamin E on streptozocin‐induced diabetes mellitus

Abstract: There is a clearly documented link between diabetic complications and lipid peroxidation. Hyperglycemia causes a reduction in levels of protective endogenous antioxidants and increases generation of free radicals. The present study was carried out to compare the protective effects of melatonin and vitamin E against streptozocin (STZ)-induced diabetes in rats. Melatonin was administered s.c. (100 microg/kg) whereas vitamin E was given i.p. (100 mg/kg) after induction of diabetes with STZ (60 mg/kg). Plasma tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
140
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(156 citation statements)
references
References 38 publications
14
140
0
2
Order By: Relevance
“…A number of studies have shown that Mel is significantly better than the classic antioxidants in resisting free radical-induced molecular destruction (Gultekin et al, 2001;Baydas et al, 2002). Beneficial antioxidant effects of Mel have been recently shown in clinical settings for several chronic diseases, including patients with rheumatoid arthritis (Forrest et al, 2007), elderly patients with primary essential hypertension (KedzioraKornatowska, 2008), and females with infertility.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that Mel is significantly better than the classic antioxidants in resisting free radical-induced molecular destruction (Gultekin et al, 2001;Baydas et al, 2002). Beneficial antioxidant effects of Mel have been recently shown in clinical settings for several chronic diseases, including patients with rheumatoid arthritis (Forrest et al, 2007), elderly patients with primary essential hypertension (KedzioraKornatowska, 2008), and females with infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin acts as antioxidant [12] and immunostimulant, and regulates mRNA levels for some specific proteins. It plays a role in the prevention of cancer, neurodegenerative diseases and diabetes complications [13].…”
mentioning
confidence: 99%
“…MT administration prevented the changes in the MDA induced by Fe administration that generated the oxidative stress in chronic hemodialysis patients to treat anemia (José et al 2001). MT caused a significant decrease in the brain, liver and kidney tissue MDA levels, which were increased because of streptozotocin-induced diabetes (Baydas et al 2002). Sahin et al (2004) found that the levels of MDA in serum, liver, heart and kidney was markedly increased in heat-stressed quail, and the levels significantly decreased by the MT supplementation.…”
Section: Discussionmentioning
confidence: 99%